Paternal history of mental illness associated with posttraumatic stress disorder among veterans. (October 2017) - Shepherd-Banigan, Megan; Kelley, Michelle L.; Katon, Jodie G.; Curry, John F.; Goldstein, Karen M.; Brancu, Mira; Wagner, H. Ryan; Fecteau, Teresa E.; Van Houtven, Courtney H.; ,; ,
Abstract: This study examined the association between parent and family reported history of non-PTSD mental illness (MI), PTSD specifically, and substance use problems, and participant clinical diagnosis of PTSD. Participants were drawn from the US Department of Veterans Affairs Mid-Atlantic Mental Illness Research, Education and Clinical Center (MIRECC) Post-Deployment Mental Health (PDMH) study (n = 3191), an ongoing multi-site cohort study of US Afghanistan and Iraq conflict era veterans. Participants who recalled a father history of PTSD had a 26-percentage point higher likelihood of meeting criteria for PTSD; while participants reporting any family history of PTSD had a 15-percentage point higher probability of endorsing symptoms consistent with PTSD. Mother history of substance use problems was associated with Veteran current PTSD, but results were sensitive to model specification. Current PTSD was not associated with family/parent history of non-PTSD mental illness, mother history of PTSD, or family/father history of substance use problems. Family history of PTSD may increase PTSD risk among veterans exposed to trauma, particularly when a father history is reported. Knowledge of family history could improve clinical decision-making for trauma-exposed individuals and allow for more effective targeting of programs and clinical services. Highlights: Examined the association between family history of mental illness and veteran PTSD. Any family and father history of PTSD was related to veteran PTSD. Family history of non-PTSD mental illness was not related to veteran PTSD. Mother history of PTSD and non-PTSD mental illness were not related to veteran PTSD. Veteran gender did not modify any of the examined relationships.